Regulatory rights of electronic equipment in criminal procedure - Sarwo Waskito; Made Warka; Krisnadi Nasution; Erny Herlin Setyorini (Technium Social Sciences Journal, 2021)
This study uses a type of normative research. The essence of Electronic Evidence in Criminal Cases is that electronic evidence must be recognized for it’s existence and legal strength, and be regulated in an integrated manner in one Law. Regulations regarding the existence and legal strength of electronic evidence must be set forth in regulations that are at the same level as law. However, in this case the Criminal Procedure Law is more integrated, and of course with the hope that this regulation can provide legal certainty for the community.